Methyltransferase like 3-mediated N6-methylatidin methylation inhibits vascular smooth muscle cells phenotype switching via promoting phosphatidylinositol 3-kinase mRNA decay - Zhao, Yongchao; Xia, Aichao; Li, Chaofu; Long, Xianping; Bai, Zhixun; Qiu, Zhimei; Xiong, Weidong; Gu, Ning; Shen, Youcheng; Zhao, Ranzun; Shi, Bei (Frontiers in Cardiovascular Medicine, 2022)
N6-methylatidine (m6A) is involved in post-transcriptional metabolism and a variety of pathological processes. However, little is known about the role of m6A in vascular proliferative diseases, particularly in vascular smooth muscle cells (VSMCs) phenotype switching-induced neointimal hyperplasia. In the current study, we discovered that methyltransferase like 3 (METTL3) is a critical candidate for catalyzing a global increase in m6A in response to carotid artery injury and various VSMCs phenotype switching. The inhibited neointimal hyperplasia was obtained after in vivo gene transfer to knock-down Mettl3. In vitro overexpression of Mettl3 resulted in increased VSMC proliferation, migration, and reduced contractile gene expression with a global elevation of m6A modification. In contrast, Mettl3 knockdown reversed this facilitated phenotypic switch in VSMCs, as demonstrated by downregulated m6A, decreased proliferation, migration, and increased expression of contractile genes. Mechanistically, Mettl3 knock-down was found to promote higher phosphatidylinositol 3-kinase (Pi3k) mRNA decay thus inactivating the PI3K/AKT signal to inhibit VSMCs phenotype switching. Overall, our findings highlight the importance of METTL3-mediated m6A in VSMCs phenotype switching and offer a novel perspective on targeting METTL3 as a therapeutic option for VSMCs phenotype switching modulated pathogenesis, including atherosclerosis and restenosis.